2020
DOI: 10.1093/ckj/sfaa027
|View full text |Cite
|
Sign up to set email alerts
|

Acute tubulointerstitial nephritis induced by checkpoint inhibitors versus classical acute tubulointerstitial nephritis: are they the same disease?

Abstract: Background The incidence of acute tubulointerstitial nephritis (ATIN) related to drugs has dramatically increased over recent years. A new subtype of ATIN, apparently different from classical drug-related ATIN, has emerged that has been related to the administration of immune checkpoint inhibitors (ICIs). We investigated these differences between ICI-related ATIN (ICI ATIN) and non-ICI-related ATIN in terms of clinical features, response to treatment with steroids and the evolution of kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Patients diagnosed with ICPI-related AIN revealed a lower plasma creatinine level accompanied by higher urinary leucocyte counts compared with the classical AIN. The serum creatinine decrement was also lower in cases of ICPI administered patients compared to non-ICPI-related ones (26).…”
Section: The Mechanisms Of Renal Toxicity Due To Icpi Treatmentmentioning
confidence: 73%
“…Patients diagnosed with ICPI-related AIN revealed a lower plasma creatinine level accompanied by higher urinary leucocyte counts compared with the classical AIN. The serum creatinine decrement was also lower in cases of ICPI administered patients compared to non-ICPI-related ones (26).…”
Section: The Mechanisms Of Renal Toxicity Due To Icpi Treatmentmentioning
confidence: 73%
“…Some investigators concluded that tubulointerstitial nephritis caused by ICIs presents some differences from the classical ATIN caused by other drugs. Draibe et al compared 13 patients with renal injury after taking ICIs with 34 patients with tubulonephritis related to other drugs and suggested that patients with ATIN related to ICIs had lower serum creatinine levels at the time of diagnosis (3.8 ± 1.0 vs 6.0 ± 4.1 mg/dL, p<0.01), and time from starting the treatment with the responsible drug to the diagnosis was longer in this group (197 ± 185 vs 114 ± 352 days, p<0.01) [65]. This suggests a milder course of kidney damage caused by ICIs.…”
Section: Possible Manifestations and Pathophysiology Of Renal Iraesmentioning
confidence: 88%
“…Injecting anti-PD1 or anti-PD-L1 antibodies not only blocked PD-1 receptor, but also triggerred T cell proliferation and cytotoxic injury of the kidney ( Dumoulin et al, 2020 ). Compared with classic acute tubulointerstitial nephritis patients, ICI-related interstitial nephritis showed similar renal histological manifestations, but there were potential differences in the development of pathological mechanisms, such as longer incubation period, lighter acute renal injury, and slower improvement of creatinine, etc ( Draibe et al, 2021 ). Retrospective cohort study showed the incidence of CKD in 2,563 cancer patients treated with ICI for more than 1 year was approximately 6.34/100 person-years, indicating that CKD events were common in ICI therapy ( Chute et al, 2022 ).…”
Section: Mechanisms Of Paraneoplastic Kidney Injurymentioning
confidence: 99%